2003
DOI: 10.1177/0022487102250285
|View full text |Cite
|
Sign up to set email alerts
|

Faculty Supply And Demand In Education

Abstract: To obtain a snapshot of current faculty supply and demand in education, a survey was distributed to the 752 American Association of Colleges for Teacher Education institutions; 408 were returned. The survey asked for vacancies, applicants, failed searches, minority hires, and reasons for shortages for 1997 to 1998 and 1998 to 1999. Vacancies averaged 4.0 per institution; applicants, 14.2 per opening. Openings increased by 34%; applicants decreased by 19%. Failed searches averaged 25%. Minority hires totaled 21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Studies report that unfilled vacancies for teacher education faculty positions are substantial, ranging from 25 percent in 1998-99 (Castle andArends 2003) to 36 percent in 2001 . Studies of special education (Smith et al 2001) and mathematics education (Reyes 2002) searches found female and older may also restrict mobility and interest in pursuing faculty positions.…”
mentioning
confidence: 99%
“…Studies report that unfilled vacancies for teacher education faculty positions are substantial, ranging from 25 percent in 1998-99 (Castle andArends 2003) to 36 percent in 2001 . Studies of special education (Smith et al 2001) and mathematics education (Reyes 2002) searches found female and older may also restrict mobility and interest in pursuing faculty positions.…”
mentioning
confidence: 99%
“…These include: (a) salaries in higher education are not competitive with market salaries (Cora-Bramble, 2006;Lopez, 2007;Phillips, 2002); (b) universities must make an active commitment by the administration (DumasHines, Cochran, & Williams, 2001;Spencer, 2003); (c) a low number of candidates is prevalent (Castle & Arends, 2003;Phillips, 2002); (d) minority faculty feel isolated (Lopez, 2007;Patton, Williams, Floyd, & Cobb, 2003); (e) there is a lack of formalized mentoring programs (Dumas-Hines, Cochran, & Williams, 2001;Subervi & Cantrell, 2007); (f) minority faculty face increased work loads (often resulting from minority faculty becoming the minority "experts" and being placed on many committees dealing in part or whole with minority issues) (Dooley, 2003); and, (h) minority faculty feel unable to effect change (Lopez, 2007).…”
Section: Recruitment Of Minority University Facultymentioning
confidence: 99%